2014
DOI: 10.1515/mammalia-2013-0023
|View full text |Cite
|
Sign up to set email alerts
|

Reoccupation of historical areas by the endangered giant river otter Pteronura brasiliensis (Carnivora: Mustelidae) in Central Amazonia, Brazil

Abstract: After decades of banning commercial hunting, the population of the endangered giant river otter in South America is no larger than 5000 animals, with slightly increasing populations, and apparent reoccupation of parts of its historical distribution. In Brazil, which may hold the largest populations, the refinement of distributional data and the conduction of censuses in Amazonia were identified as essential for the conservation of the species. To confirm if the species was, in fact, reoccupying its historical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…However, Carter and Rosas (1997) suggested that these numbers are underestimates, based on information from Schweizer (1992) for the southern portion of the Pantanal wetland, Brazil. Nowadays, few viable populations persist outside the Pantanal and the Amazonian regions (Chehébar, 1990), which is supported by recent surveys conducted in the Brazilian Amazon (Lima et al, 2013;Rosas et al, 2007), Pantanal 2 (Ribas, 2004;Leuchtenberger, 2012) and Araguaia River (see http://www.araguaia.org/ cantao/Projeto_Ariranha_2.html).…”
Section: Introductionmentioning
confidence: 88%
“…However, Carter and Rosas (1997) suggested that these numbers are underestimates, based on information from Schweizer (1992) for the southern portion of the Pantanal wetland, Brazil. Nowadays, few viable populations persist outside the Pantanal and the Amazonian regions (Chehébar, 1990), which is supported by recent surveys conducted in the Brazilian Amazon (Lima et al, 2013;Rosas et al, 2007), Pantanal 2 (Ribas, 2004;Leuchtenberger, 2012) and Araguaia River (see http://www.araguaia.org/ cantao/Projeto_Ariranha_2.html).…”
Section: Introductionmentioning
confidence: 88%
“…Owing to their biology and behaviour, P. brasiliensis is more susceptible to persecution by fishers and hunters than L. longicaudis, whose populations persisted at low densities during this period (Pimenta, Antunes, et al, 2018). Since international trade restrictions and conservationist efforts were implemented in the mid-1970s, P. brasiliensis populations have shown signs of recovery in many parts of their range (Lima, Marmontel, & Bernard, 2014b;Pimenta, Gonçalves, Shepard, Macedo, & Barnett, 2018;Recharte & Bodmer, 2009), although in some regions this species is still considered extinct or nearly so, or with declining population trends (Groenendijk et al, 2015).…”
Section: Fishing and Harvesting Of Aquatic Resources/hunting And Collecting Of Terrestrial Animals: Intentional Usementioning
confidence: 99%
“…Araguaia River (Araújo & da Silva, 2014) Tocantins River (Paschoalini et al, 2020) Unknown Decline continent-wide. Variable trends along Amazon Basin, with some recovering populations (Groenendijk et al, 2015) Recovering: Brazil (Amanã Lake; Lima et al, 2014b); Içana River (Pimenta, Gonçalves, et al, 2018); Peru (Manu River; Groenendijk et al, 2014); Yavarí-Mirín and Yavarí rivers (Recharte & Bodmer, 2009); Bolivia (Northern La Paz; Ayala, Wallace, Viscarra, & Jurado, 2015) Declining: Peru (Madre de Dios, outside PAs; Mendoza et al, 2017)…”
Section: Inia Araguaiaensismentioning
confidence: 99%
“…Protected continent-wide, some populations are showing signs of slow recovery after the pelt trade era. Over the last few years, the reappearance of populations in Peru, Brazil (Amazonia, Cerrado and Pantanal), Colombia, Ecuador and Bolivia has been documented or observed (Recharte and Bodmer, 2009;Zambrana et al, 2012;Lima et al, 2013;Marmontel, pers. obs; this issue) 1,4 .…”
Section: Historical Perspectivementioning
confidence: 99%